1998
DOI: 10.1159/000069427
|View full text |Cite
|
Sign up to set email alerts
|

Biotherapy with the Pineal Immunomodulating Hormone Melatonin versus Melatonin plus <i>Aloe vera</i> in Untreatable Advanced Solid Neoplasms

Abstract: The possibility of natural cancer therapy has been recently suggested by advances in the knowledge of tumor immunobiology. Either cytokines such as IL-2, or neurohormones, such as the pineal indole melatonin (MLT), may activate anticancer immunity. In addition, immunomodulating substances have also been isolated from plants, particularly from Aloe vera. Preliminary clinical studies had already shown that MLT may induce some benefits in untreatable metastatic solid tumor patients, whereas, for the time being, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 13 publications
0
33
0
2
Order By: Relevance
“…Topical application inhibited contact hypersensitivity and delayed type hypersensitivity suppression by UV radiation in mice. It preserved the number and morphology of irradiated Langerhans and dendritic epidermal cells in skin (Lissoni et al 1998). It is demonstrated that the administration of with pineal indole melatonin Aloe vera enhances the therapeutic results in patients with advanced solid tumors.…”
Section: Biological Activities Of Aloe Veramentioning
confidence: 87%
“…Topical application inhibited contact hypersensitivity and delayed type hypersensitivity suppression by UV radiation in mice. It preserved the number and morphology of irradiated Langerhans and dendritic epidermal cells in skin (Lissoni et al 1998). It is demonstrated that the administration of with pineal indole melatonin Aloe vera enhances the therapeutic results in patients with advanced solid tumors.…”
Section: Biological Activities Of Aloe Veramentioning
confidence: 87%
“…Both treatments were well tolerated. This preliminary study would suggest that natural cancer therapy with melatonin plus Aloe vera extract may produce some therapeutic benefits, at least in terms of stabilization of disease and survival, in patients with advanced solid tumors, for whom no other standard effective therapy is available [16] . The advances in the analysis of tumor immunobiology suggest the possibility of biological manipulating the efficacy and toxicity of cancer chemotherapy by endogenous or exogenous immunomodulating substances.…”
Section: Preliminary Clinical Studymentioning
confidence: 95%
“…Foi possível evidenciar uma maior taxa de sobrevivência e de regressão do tumor, além de alívio da fadiga e astenia, quando comparados ao grupo controle. Outro estudo preliminar, feito com pacientes com câncer em estágio avançado demonstrou maior estabilização da doença e aumento do tempo de sobrevivência no grupo tratado com a combinação da A. vera e do hormônio melatonina (Lissoni et al, 1998).…”
Section: Atividade Antineoplásicaunclassified